Prevalence and associated factors of contraceptive discontinuation among reproductive-age women in Ethiopia: using 2016 Nationwide Survey Data - Birye Dessalegn Mekonnen; Chalachew Adugna Wubneh (BMC, 2020)
Abstract Background Contraceptive discontinuation for reasons other than the desire for pregnancy is associated with mistimed and unwanted pregnancies, unwanted births and unsafe abortions which has increased risks of maternal morbidity and mortality. However, research on the identification of factors that are associated with contraceptive discontinuation in Ethiopia is limited. Therefore, this study aimed to determine the prevalence of contraceptive discontinuation and associated factors among reproductive-age women in Ethiopia, using recent national survey data. Methods A population-based cross-sectional study was conducted using secondary data analysis from of 2016, Ethiopian Demographic Health Survey. A total of 10,871 reproductive-age women were included. The analysis was performed using SPSS version 20 statistical package. Bivariate and multivariate logistic regression analysis was conducted to examine significant factors of contraceptive discontinuation, and statistical significance was declared at p-value < 0.05. Results The prevalence of discontinuation for all contraceptives methods among reproductive-age women was 32.2% (95% C.I 31.2, 33.1). Rural residence (AOR = 1.94, 95% C.I 1.65, 2.28), women with no formal education (AOR = 1.68, 95% C.I 1.30, 2.17), women having no children (AOR = 1.95, 95% C.I 1.19, 3.58), husband desire for children (AOR = 2.57, 95% C.I 2.03, 3.26), women self-decision when using a contraceptive (AOR = 0.54, 95% C.I 0.38, 0.77), joint decision when using a contraceptive (AOR = 0.38, 95% C.I 0.29, 0.48), didn't discuss about FP with healthcare worker (AOR = 1.28, 95% C.I 1.06, 1.54) and didn't get information about side effects (AOR = 2.01, 95% C.I 1.59, 2.52) were factors significantly associated with contraceptives discontinuation. Conclusion The prevalence of contraceptive discontinuation among reproductive-age women was high and multiple factors determined it. Thus, counseling on side effects, availability of other contraceptive methods, and partner involvement in decision-making process by health care providers are strongly recommended. In addition, women empowerment should be promoted so that women are able to liberally decide on when and how many children they wish to have.